USING MINI SERIES FLASH CARDS TO ATTRACT STUDENTS’ IN LEARNING READING - Diah Paramita Sari; Arita Destianingsih (Politeknik Negeri Bengkalis, 2018)
Abstract: Learning Reading for junior high schools can use a variety of media. Among them is by using the Flashcard Mini Series. This is a media or tool that contains images and writing to facilitate students in reading lessons. Inside the flashcard are words to remind students of what they have just read. This flashcard can also be used to warm up for students before reading or discussing a reading. This study aims to discuss one way to solve students’ problem in comprehending a text. The process of using miniseries flash cards is students are grouped into approximately 5 people. Then, the teacher gave a miniseries flashcards to each group. The teacher gives a text containing the contents of the miniseries flashcards. After that, students are given a new text and miniseries flashcards containing new material. Each group is given a different text. After completing the answer, the text and flashcard miniseries are given to other groups; they also do the same. The miniseries flashcards are answered in turn by each group. Miniseries flashcards as learning media are able to provide an understanding of reading where the media is able to represent the contents of the reading so that students understand the text easily. Keywords: Reading Comprehension, Miniseries Flashcards